Phasing out coal - An impact analysis comparing five large-scale electricity market models - Arne Pöstges; Michael Bucksteeg; Oliver Ruhnau; Diana Böttger; Markus Haller; Eglantine Künle; David Ritter; Richard Schmitz; Michael Wiedmann (ZBW - Leibniz Information Centre for Economics, 2021)
Climate target achievement has a crucial influence on the modelling and the decision processes in the energy sector. It induced the development of several policy instruments to mitigate greenhouse gas emissions, including administrative and market-based mechanisms for phasing out coal-fired generation technologies. In order to analyse such instruments, electricity market and energy system models are widely used. However, results and corresponding recommendations largely depend on the formulation of the respective model. This motivates a systematic comparison of five large-scale electricity market models which are applied to European scenarios considering the period until 2030. An evolved diff-in-diff approach is proposed to analyse the effects of two coal phase-out strategies. This contribution expands on that of earlier studies and provides some more general takeaways for both modellers and decision-makers. For instance, the evolved diff-in-diff analysis shows the influence of the reference scenario when evaluating a policy instrument. Furthermore, the importance of technical aspects such as constraints for combined heat and power plants are discussed and implications regarding three dimensions (economic, environmental, and security of supply) are presented.
Keywords: P11; P28; Q4; Q48; Q51; 330; model comparison; coal phase-out; electricity market model; energy policy